2016
DOI: 10.2147/ceor.s121093
|View full text |Cite
|
Sign up to set email alerts
|

Costs of adverse events associated with erlotinib or afatinib in first-line treatment of advanced EGFR-positive non-small cell lung cancer

Abstract: ObjectivesEpidermal growth factor receptor–tyrosine kinase inhibitors (EGFR-TKIs) are an established treatment for advanced non-small cell lung cancer (NSCLC) with EGFR mutation. According to published meta-analyses, no significant efficacy differences have been demonstrated between erlotinib and afatinib. However, the incidence of EGFR–TKI-related adverse events (AEs) was lower with erlotinib. This study compares the cost of management of the AEs associated with these two drugs from the perspective of the Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
(52 reference statements)
0
7
1
8
Order By: Relevance
“…Although previous research has suggested a lower incidence of adverse events with erlotinib compared to afatinib 21 , our analysis of real-world data showed no differences in HCRU that might have been expected given potential differences in tolerability profiles. Fewer afatinib patients experienced at least one inpatient or outpatient visit compared to erlotinib patients, whereas the proportion of patients requiring at least one outpatient office or other outpatient visit was similar between afatinib and erlotinib.…”
Section: Discussioncontrasting
confidence: 77%
“…Although previous research has suggested a lower incidence of adverse events with erlotinib compared to afatinib 21 , our analysis of real-world data showed no differences in HCRU that might have been expected given potential differences in tolerability profiles. Fewer afatinib patients experienced at least one inpatient or outpatient visit compared to erlotinib patients, whereas the proportion of patients requiring at least one outpatient office or other outpatient visit was similar between afatinib and erlotinib.…”
Section: Discussioncontrasting
confidence: 77%
“…Despite these limitations, there are notable advantages to implementation of an assay that increases first-line use of EGFR TKIs, including cost savings relative to up-front treatment with chemotherapy and the potential to induce faster and more robust responses in symptomatic patients. 4,3438 Although EGFR -mutant NSCLC is classically regarded as an indolent disease, many patients present with widely metastatic disease (Data Supplement). 39,40 The superior efficacy of EGFR TKIs relative to chemotherapy against brain metastases and the potential to defer brain radiation for these patients underscore the importance of rapid identification of EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Solo a fronte di una riduzione del tasso di incidenza della diarrea di grado ≥3, afatinib risulterebbe costoneutrale rispetto a erlotinib (dal 9% al 2,9%) e a gefitinib (dal 9% al 6,6%). Il risultato del confronto di erlotinib con afatinib viene confermato anche da una recente esperienza spagnola (41). Nello specifico, lo studio spagnolo, condotto con una metodologia simile alla nostra, ha determinato un maggiore costo di afatinib rispetto a erlotinib nella gestione degli EA associati al trattamento di prima linea del NSCLC in stadio avanzato con mutazione EGFR (41 ALT = alanina aminotransferasi; SSN = Sistema Sanitario Nazionale.…”
Section: Discussioneunclassified
“…Il risultato del confronto di erlotinib con afatinib viene confermato anche da una recente esperienza spagnola (41). Nello specifico, lo studio spagnolo, condotto con una metodologia simile alla nostra, ha determinato un maggiore costo di afatinib rispetto a erlotinib nella gestione degli EA associati al trattamento di prima linea del NSCLC in stadio avanzato con mutazione EGFR (41 ALT = alanina aminotransferasi; SSN = Sistema Sanitario Nazionale. a Sono state considerate due confezioni da 10 cpr da 25 mg al prezzo al pubblico per confezione di €5,87.…”
Section: Discussioneunclassified